Strategi Mengatasi Kesulitan Belajar Membaca Pada Kelas Awal Sekolah Dasar - Abdullah Munawir Nasution; Abdi Maulana; Maria Grasella Silaban; Khairunnisa Khairunnisa (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to develop strategies for overcoming failure in learning to read in early elementary school students. The research results show that effective strategies for overcoming failure in learning to read involve the use of visual media, individual guidance, and the use of language that is easy to understand. The conclusion of this research is that effective strategies for overcoming failure in learning to read can improve the reading ability of students in the early grades of elementary school. The suggestion of this research is that teachers and parents must use strategies to overcome failure in learning to read effectively to improve the reading ability of students in the early grades of elementary school.